Quantitative and Qualitative Analysis of Traditional Practices and Gender-Based Violence - Ojong-Ejoh, Mary U.; Cobham, Glory; Iloeje, Ijeoma A.; Tangban, Egbe E. (Lembaga Penelitian dan Pengembangan Teknologi dan Rekayasa, Yayasan Ahmar Cendekia Indonesia, 2021)
This study assessed if traditional practices such as early marriage, Female genital cutting and honour violence perpetuate gender-based violence in Obudu Local Government Area of Cross River State, Nigeria. The study adopted the quasi-experimental research design in selecting four hundred samples from Obudu Local Government Area using stratified and purposive sampling technique. The questionnaire and interview guide were the instruments used for data collection. Quantitative data collected was analyzed using multiple regression, while qualitative data were thematically analyzed. Out of the 400 instruments distributed only 331 was returned and was used for analysis. The result from the analysis revealed that Traditional practices such as early marriage, Female genital cutting, honour violence perpetuate gender-based violence in Obudu Local Government Area of Cross River State, Nigeria. The study recommends amongst others that the government through legislation has to increase women enrolment and access to education at all level.